1976
DOI: 10.1161/01.str.7.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computerized tomography and radionuclide imaging in "stroke".

Abstract: SUMMARY Forty patients were studied by computerized tomography and by radionuclide brain imaging. The final diagnosis was infarction in 29 patients, intracerebral hematoma in seven, acute SAH in one, and old cerebrovascular accidents in three. CT was far superior to RN in detecting intracerebral hematomas and distinguishing them from cerebral infarction. The results of CT and RN tests were comparable regarding the percentage of abnormalities. However, the results in the same patients were not identical in 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A number of studies compasing CT and 99mTc radionuclide imaging have indicated a similar time course for visualisation of BBB dysfunction in cases of cerebral infarction [19][20][21][22]. The acute phase was most likely to yield negative results and the 10-to 14-day period was considered optimal for obtaining CT enhancement or 99mTc accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies compasing CT and 99mTc radionuclide imaging have indicated a similar time course for visualisation of BBB dysfunction in cases of cerebral infarction [19][20][21][22]. The acute phase was most likely to yield negative results and the 10-to 14-day period was considered optimal for obtaining CT enhancement or 99mTc accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The percent negative CT scans in cerebral infarctions varies a great deal in different studies [1,2,4,13,14], Many potentially interfering factors may influence the results: technical equipment, using contrast injec tion, time of examination after ictus, exclud ing or including posterior fossa infarctions, etc. After considering such factors, there still remains a certain percentage of negative CT scans.…”
Section: Causes O F Negative Ct Scans In Cerebrovascular Diseasementioning
confidence: 99%